Do Stakeholder Pressure and Profitability Matter to The Quality of Sustainability Report? - Pratiwi, Andien Mirza; Lastiati, SE.Ak., MHRM., M.Ed.St., CA, Anies (Adpebi Science Series, 2024)
This research aims to examine the relationship between stakeholder pressure (SP) and sustainability reporting quality (SRQ). This research method is quantitative. The sample for this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) in 2020-2022. The research data source uses financial report data, annual reports, and sustainability reports. Stakeholders pressure' impact, with its 4 main indicators, on the quality of the company's sustainability report. Moreover, this study also evaluate the role of profitability in strengthening the stakeholders pressure's influence on sustainability reporting quality. The results show that stakeholder pressure is proven to have a positive and significant effect on sustainability reporting quality and the profitability also strengthens the effect.